2015
DOI: 10.1016/j.physio.2015.03.2066
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in load carriage injuries of Australian army soldiers

Abstract: Background: With the removal of gender restrictions and the changing nature of warfare potentially increasing female soldier exposure to heavy military load carriage, the aim of this research was to determine relative risks and patterns of load carriage related injuries in female compared to male soldiers. Methods: The Australian Defence Force Occupational Health, Safety and Compensation Analysis and Reporting workplace injury database was searched to identify all reported load carriage injuries. Using key sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
0
14
2
Order By: Relevance
“…Of note, no differences in the severity of injuries between the genders were reported. This contrasts the findings of Orr et al [35], who found that while male and female soldiers suffered similar levels of injuries due to occupational load carriage, female personnel were 2.4 times more likely to suffer a 'serious personal injury' than male personnel. Noting that the research by Orr et al [35], was of a single task (load carriage) in a military population, potential differences in severity are reported by Hua et al [77], who found that female police officers, in general, attended a greater number of inhouse physiotherapy treatments than male officers (8.25 ± 5.12 vs. 6.57 ± 4.03 treatments respectively).…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Of note, no differences in the severity of injuries between the genders were reported. This contrasts the findings of Orr et al [35], who found that while male and female soldiers suffered similar levels of injuries due to occupational load carriage, female personnel were 2.4 times more likely to suffer a 'serious personal injury' than male personnel. Noting that the research by Orr et al [35], was of a single task (load carriage) in a military population, potential differences in severity are reported by Hua et al [77], who found that female police officers, in general, attended a greater number of inhouse physiotherapy treatments than male officers (8.25 ± 5.12 vs. 6.57 ± 4.03 treatments respectively).…”
Section: Discussioncontrasting
confidence: 98%
“…This contrasts the findings of Orr et al [35], who found that while male and female soldiers suffered similar levels of injuries due to occupational load carriage, female personnel were 2.4 times more likely to suffer a 'serious personal injury' than male personnel. Noting that the research by Orr et al [35], was of a single task (load carriage) in a military population, potential differences in severity are reported by Hua et al [77], who found that female police officers, in general, attended a greater number of inhouse physiotherapy treatments than male officers (8.25 ± 5.12 vs. 6.57 ± 4.03 treatments respectively). Differences in these findings may be explained by several factors including, a lack of detail in regard to rating the severity of the injuries entered into the database, differences in reporting processes (e.g., self-reported, as was the case in this study) versus point-of-care (i.e.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…[1][2][3] Repetitive and prolonged load carriage can place significant strain on the musculoskeletal system, increasing the risk of acute and chronic overuse injuries, in particular for untrained soldiers. 3,4 In an attempt to reduce this risk, Representative Military Tasks (RMTs) have been developed to assess a soldier's physical status and combat readiness which replicate the physical demands of specific military tasks, but in a more practical and safe manner. 5,6 A prerequisite for applicants wishing to join the Infantry in the British Army is to complete and pass three RMTs to a required standard before basic training, namely a 1.5 mile run (to best effort), a Single Lift (SL; capped at 40 kg; Powerbag TM from the floor onto a 1.45 m platform), and a bilateral Water Can Carry (WCC; 20 kg on each hand, capped at a distance of 150 m).…”
Section: Introductionmentioning
confidence: 99%